A qualitative analysis of communication workflows between adult day service centers and primary care providers. (29th December 2021) - Zhong, Jie; Boafo, Jonelle; Brody, Abraham A; Wu, Bei; Sadarangani, and Tina
Abstract: Objectives: Our study documented communication workflows across adult day care centers (ADCs) and primary care providers (PCPs) around complex needs of persons living with dementia (PLWD). We also identified barriers and facilitators to productive communication in clinical decision support and clinical information systems. Materials and Methods: We conducted 6 focus groups with ADC staff ( N  = 33) and individual semistructured interviews with PCPs ( N  = 22) in California. The eHealth Enhanced Chronic Care Model was used to frame the directed qualitative content analysis. Results: Our results captured cumbersome and ineffective workflows currently used to exchange information across PCPs and ADCs. Stakeholders characterized current communication as (1) infrequent, (2) delayed, (3) incomplete, (4) unreliable, (5) irrelevant, and (6) generic. Conversely, communication that was bidirectional, relevant, succinct, and interdisciplinary was needed to elevate the standard of care for PLWD. Discussion and Conclusion: ADCs possess a wealth of information that can support clinical decision-making across community-based providers involved in the care of PLWD, especially PCPs. However, effective information exchange is mired by complicated workflows that rely on antiquated technologies (eg, facsimile) and standard templates. Current information exchange largely focuses on satisfying regulatory guidelines rather than supporting clinical decision-making. Integrating community-based services into the health care continuum is a necessary step in elevating the standard of care for PLWD. In the absence of interoperable electronic health records, which may not be financially viable for ADCs, other options, such as mobile health, should be explored to facilitate productive information exchange of personalized relevant information.